The natural history of WPW syndrome. (9th March 2015) - Pappone, Carlo; Vicedomini, Gabriele; Manguso, Francesco; Baldi, Mario; Petretta, Andrea; Giannelli, Luigi; Saviano, Massimo; Pappone, Alessia; Ionescu, Bogdan; Ciaccio, Cristiano; Vitale, Raffaele; Cuko, Amarild; et al.
Abstract: The aim of this article is to understand the natural history of WPW syndrome to prevent sudden death is important to clinicians in establishing accurate prognosis and appropriate treatment. We report our experience on untreated WPW patients purely looking at the natural history of the disease. In a 15-year period (1995–2010), among 11 237 WPW patients referred to our Arrhythmology Department, a total of 1847 selected patients (820 symptomatic) underwent electrophysiological testing without ablation and were followed for a median (25th–75th) follow-up of 8 (5–8) years. During follow-up, malignant arrhythmias (MA) occurred in 16 patients (0.9%) of whom 14 (1.4%) were initially asymptomatic and two (0.2%) symptomatic ( P = 0.01). Potentially MA developed in 143 patients (7.7%) without difference between asymptomatic and symptomatic population ( P = 0.663). Benign recurrences developed in 295 patients (16%) while ventricular pre-excitation disappeared in 356 patients (19.3%) of whom 155 were initially asymptomatic. All patients were successfully ablated after arrhythmia occurrence. Patients with MA had similar accessory pathways antegrade refractory periods (AP-AERP) ( P = 0.064) and more frequently inducible atrioventricular reciprocating tachycardia triggering atrial fibrillation (AVRT-AF) than those with potentially MA ( P < 0.001). Symptoms did not predict MA, which were predicted by AP-AERP (HR 0.912, 95% CI 0.887–0.939, P < 0.001) and AVRT-AF (HR 8.306, 95% CI 2.269–30.405, P = 0.001). The natural history of WPW syndrome and the risk of sudden death essentially depend on intrinsic electrophysiological accessory pathway properties rather than on symptoms and electrophysiologic testing is the gold standard to identify patients at risk. The Authors encourage more intensive screening programs to identify asymptomatic patients at risk for prophylactic ablation.